Acute Toxicity, Respiratory Reaction, and Sensitivity of Three Cyprinid Fish Species Caused by Exposure to Four Heavy Metals - Wang, Hongjun; Liang, Youguang; Li, Sixin; Chang, Jianbo (PLOS ONE, 2013)
Using 3 cyprinid fish species zebra fish, rare minnow, and juvenile grass carp, we conducted assays of lethal reaction and ventilatory response to analyze sensitivity of the fish to 4 heavy metals. Our results showed that the 96 h LC50 of Hg2+ to zebra fish, juvenile grass carp, and rare minnow were 0.14 mg L−1, 0.23 mg L−1, and 0.10 mg L−1, respectively; of Cu2+0.17 mg L−1, 0.09 mg L−1, and 0.12 mg L−1 respectively; of Cd2+6.5 mg L−1, 18.47 mg L−1, 5.36 mg L−1, respectively; and of Zn2+44.48 mg L−1, 31.37 mg L−1, and 12.74 mg L−1, respectively. Under a 1-h exposure, the ventilatory response to the different heavy metals varied. Ventilatory frequency (Vf) and amplitude (Va) increased in zebra fish, juvenile grass carp, and rare minnows exposed to Hg2+ and Cu2+ (P<0.05), and the Vf and Va of the 3 species rose initially and then declined when exposed to Cd2+. Zn2+ had markedly different toxic effects than the other heavy metals, whose Vf and Va gradually decreased with increasing exposure concentration (P<0.05). The rare minnow was the most highly susceptible of the 3 fish species to the heavy metals, with threshold effect concentrations (TEC) of 0.019 mg L−1, 0.046 mg L−1, 2.142 mg L−1, and 0.633 mg L−1 for Hg2+, Cu2+, Cd2+, and Zn2+, respectively. Therefore, it is feasible to use ventilatory parameters as a biomarker for evaluating the pollution toxicity of metals and to recognize early warning signs by using rare minnows as a sensor.